Kant’s Categorical Schematization of Perception - Majka, Wojciech (Wydawnictwo Uniwersytetu Rzeszowskiego, 2017)
For Immanuel Kant knowledge is seen to be strictly confined to the senses that find information that is later processed by the cognitive categories of human understanding. Ipso facto, we never see the objective character of things in themselves but only the representations of things in sensation. Morality, as the outstanding feature of human beings, is based on the notion of the good will and the categorical imperative, which urges us to act ethically on account of our collective being in culture.
Keywords: Perception; Subjectivity; Objectivity; Sensation; Understanding; Determinism; Freedom; Causation; Time; Space